Pengembangan Mobile Learning Berbasis RADEC Pada Materi Sistem Pencernaan untuk Melatih Literasi Digital dan Hasil Belajar Kognitif Siswa - Lisa Meidya; Sri Haryani; Nanik Wijayati; Decky Avrilianda; Bambang Subali (Jurnal Pendidikan Biologi Undiksha, 2024)
Both teachers and students already have technology such as smartphones but have not yet used them as learning media. Therefore, the development of mobile learning media has become an inspiration. The purpose of this research and development is to create, validate, and test the effectiveness of mobile learning media on the digestive system to train 11th-grade students at SMAN 1 Gondanglegi in digital literacy and cognitive learning outcomes. Analysis, design, development, implementation, and evaluation are the steps included in the approach used, which is based on the Lee and Owens model. The implementation stage has not yet been conducted in this research and development. Analysis of the results from each test shows that the developed product is highly valid, practical, and can be used to teach digital literacy and cognitive learning outcomes of students. The results of the media expert validation were 94%; the subject matter expert, biology education practitioner, and learning device expert each had 100%.